IMPLEMENTATION OF INTERACTIVE LEARNING BASED ON MULTIMODAL TEXTS TO IMPROVE STUDENTS’ CRITICAL THINKING SKILLS - Mulyati Mulyati; Arwan Arwan; Bagus Muhammad Fadli (Program Studi PGSD Universitas Flores, 2026)
Students’ critical thinking skills in expository-text learning require further development because classroom instruction tends to remain teacher-centered and relies on single-mode verbal texts. This study aimed to analyze the improvement of students’ critical thinking skills through the implementation of interactive learning based on multimodal texts. The study employed a Classroom Action Research design based on the Kemmis and McTaggart model and was conducted in two cycles involving 20 students. Each cycle comprised planning, action, observation, and reflection. Data were collected through tests, observations, and documentation and were analyzed using descriptive quantitative and interactive qualitative techniques. The results showed gradual improvements in both mean scores and classical learning mastery. The mean score and mastery percentage increased from 56.15 and 25% in the pre-cycle stage to 70.40 and 50% in Cycle 1 and to 80.85 and 90% in Cycle 2. These improvements were associated with the use of written texts, images, infographics, audio, and video as interconnected sources of information analyzed through discussions, stimulating questions, feedback, and instructional scaffolding. Therefore, interactive learning based on multimodal texts can improve expository-text instruction and descriptively enhance students’ critical thinking skills, although the findings remain contextual to a single classroom.